MANFAAT SISTEM INFORMASI AKUNTANSI UNTUK EFEKTIVITAS KEUANGAN, MANAJEMEN, DAN ORGANISASI - Edi, Edi; Wahyuningrum, Evita Apilliyani (LLDIKTI Wilayah X, 2017)
The purpose of this study is to analyze the benefits of the accounting information system for financial performance, performance management and organizational performance at Rural Banks in Batam. The dependent variables of this research are financial performance, management performance, and organizational performance. Independent variable of this research is accounting information system. The object of this research use purposive sampling method to BPR registered in Bank Indonesia which is position of Finance and Accounting Manager, Operational Manager and Branch Manager. This study uses multiple linear regression to analyze the effect of the independent variable to the dependent variable. The results obtained that the accounting information system has a significant influence on financial performance, performance management and organizational performance.